A reliability-centered methodology for identifying renovation actions for improving resilience against heat waves in power distribution grids. (May 2022) - Bellani, Luca; Compare, Michele; Zio, Enrico; Bosisio, Alessandro; Greco, Bartolomeo; Iannarelli, Gaetano; Morotti, Andrea
Abstract: In performance-based regulation paradigms, national authorities offer incentives to distribution system operators to develop plans for increasing the network resilience against natural hazards, such as heat waves, hurricanes, rain bombs, flooding. In this paper, we propose an approach, compliant with the Italian performance-based regulation framework, to prioritize renovation actions on sections of electrical power distribution networks for improving resilience against heat waves. The approach is made up of three steps, each addressed through a novel methodology: (i) define the hazard of interest, i.e., heat waves; (ii) estimate the reliability of the network branches; (iii) prioritize the renovation interventions on the network to improve its resilience. The methodology has been applied to the medium voltage distribution network of Milano, Italy, yielding the identification of prioritized intervention actions to submit to the authority for incentives. Highlights: We prioritize renovation actions on EPDNs for improving resilience against heat waves. The approach is made up of three steps and compliant with the Italian PBR framework. Steps: define heat wave; estimate EPDN branch reliability; prioritize interventions. The methodology is applied to the MV network of Milano, Italy.